1980
DOI: 10.1002/cjce.5450580114
|View full text |Cite
|
Sign up to set email alerts
|

Energetic aspects of turbulence promotion applied to electrolysis processes

Abstract: This paper presents a simple and rational method for determining how much hydrodynamic factors influence the rate of production in electrochemical systems using turbulence promoters in various alternative flow conditions. Empirical and theoretical data correlations of limiting current densities (or mass transfer coefficients) and pressure drops are presented in unobstructed channels as well as for eddying flow induced by different types of eddy promoters. Based on the dimensional analysis and on the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…SPC represents the mechanical energy required to overcome the fluid's pressure drop per unit length of the domain [39]. Storck and Hutin [40] define SPC as…”
Section: Specific Power Consumption (Spc)mentioning
confidence: 99%
“…SPC represents the mechanical energy required to overcome the fluid's pressure drop per unit length of the domain [39]. Storck and Hutin [40] define SPC as…”
Section: Specific Power Consumption (Spc)mentioning
confidence: 99%
“…where P is the pressure drop over the channel, L is the channel length, A is the cross-section area of the channel, and u is the mean liquid velocity in the channel. A similar approach was described by Storck and Hutin [19] in which results were presented in the plots of k m versus SPC.…”
Section: Optimization Of Spacersmentioning
confidence: 99%
“…[1][2][3][4] A number of researchers examined experimentally the effect of flow, which is obstructed by filaments, in electrochemical cells. [5][6][7][8][9][10][11][12][13] The filaments increased both the local and the overall mass-transfer rate. The results showed that high wall shear stresses and the reattachment regions of recirculation zones increase the local mass-transfer rate.…”
Section: Introductionmentioning
confidence: 99%
“…Spacer nets are used in spiral-wound membrane modules to keep the membrane leaves apart and to reduce the wall concentration by enhancing the mass transfer. A number of researchers examined experimentally the effect of flow, which is obstructed by filaments, in electrochemical cells. The filaments increased both the local and the overall mass-transfer rate. The results showed that high wall shear stresses and the reattachment regions of recirculation zones increase the local mass-transfer rate.…”
Section: Introductionmentioning
confidence: 99%